Goal programming model for production planning in a toothpaste factory (2008)
The GP model was developed for production planning in a toothpaste factory. Two objectives were distinguished: minimization of processing cost, and maximization of the capacity utilization of production facilities. Two priority structures were used to explore the trade-off options. When processing cost minimization was assigned the first priority, the utilizations of Processing Plant 1 and Filling Machine 2 were 20.32% and 0.18% respectively. When capacity utilization was assigned first priority, the processing cost increased by 7.55% but capacity utilization improved. The least utilized facility was Filling Machine 1 with a utilization of 43.85%.